ANALISA FAKTOR YANG MEMPENGARUHI KONSUMEN SES AB DALAM PEMILIHAN MEREK KOPI BUBUK DI DKI JAKARTA - Faisyal Faisyal; Ina Agustini Murwani (Bina Nusantara University, 2008)
This research has two main purposes, that are to identify attributes influencing consumers in choosing a coffee brand and to know the perceptual coffee map in current market. Data for these research were obtained from a structured questionnaire with about 150 correspondents in DKI Jakarta whose age ranged from 20 – 50 year-old with SES AB. The statistical techniques used in this research were descriptive statistics, correlational analysis, and correspondence analysis. Some attributes influencing consumers in the selection of instant coffee, starting from their level of significance, include taste, easy to get, achievable price, made from chosen coffee seeds, good aromatic, available in sachettes, refined coffee powder, make awaking, popular brand, and interesting advertisement. From perceptual map above we can see that some of coffee brand have almost same attributes in coffee consumer. Perception for ABC mocca coffee is coffee with delicious taste and always available in sachette. Perception for Kapal Api milk coffee is coffee with interested advertising. Perception for Kapal Api special and ABC coffee plus is populary brand. While, Kapal Api special mix perceptioning by society is coffee with effectively make awaking. Singa Coffee, Ayam Merak coffee and Torabika have same characteristics are refined coffee powder and easy to get. Lastly, Torabika Duo + susu coffee and Kapal Api Mocca have same characteristic is delicious taste.